400. Secondary Infections in COVID-19 Patients Receiving Tocilizumab in a Community Hospital. (31st December 2020) - Usiak, Shauna; DiFilippo, Laurie; Frattellone, Meredith; Kincart, Mary; Kerr, Christine
Abstract: Background: Secondary bacterial/fungal infection in patients with pandemic strains of Influenza has been well documented in the literature. Little is known about the development of secondary bacterial or fungal infections in patients with COVID-19. Additionally, COVID patients receiving tocilizumab as treatment may be at higher risk for developing a secondary infection due to theoretical risk of immunosuppression. Table 1 Table 2 Methods: A retrospective analysis of all COVID positive patients admitted to a 128 bed community hospital in Westchester County, NY from March 1 – May 31, 2020. The data was analyzed to determine incidence of secondary infections based on positive cultures in patients and further stratified based on receipt of tocilizumab. Results: Out of 445 COVID positive patients reviewed, 69 (15.5%) had positive bacterial/fungal cultures. Average age of the patient population reviewed was 64 (range 1 – 106) and 60% of the patients were male. As of May 31, 2020, 114 of the patients had expired, 281 were discharged, 23 were transferred, and 27 were still admitted to the hospital. Of the 445 total patients, 42 received at least 1 dose of tocilizumab. Out of those patients, 6 patients (14.3%) had subsequent positive cultures. (Table 1) This was not statistically significant ( p = 0.8185 ). Most common positive specimens were in urine (n=38), blood (n=33), and respiratory specimens (n=20). Most commonly found co-pathogens were Escherichia coli (n=22), Coagulase-negative staphylococci (n=11), and Pseudomonas aeruginosa (n=9). Of the 69 patients with positive cultures, 27 received ICU level of care. (Table 2) Conclusion: A small retrospective study found that the incidence of bacterial or fungal co-infection for COVID positive patients was high but did not find receipt of tocilizumab was associated with secondary infections. This suggests areas for future study and further investigation as hospitals consider use of immunomodulatory therapies in the treatment of COVID-19. Disclosures: All Authors : No reported disclosures